Ultimate design load of thin–walled stub columns. (4th August 2014) - Chou, S.M; Chai, G.B
This paper presents an alternative design procedure suitable for estimating the ultimate load of thin–walled stub–column structures. Standard design procedures are developed for the post–buckling analysis of these structures using the finite element method. The ultimate loads for the steel columns under compressive loads are found using a nonlinear finite element analysis. These numerical results are compared with experimentally obtained ultimate loads. Predictions using the design code BS5950: Part 5 (1987) are also included for completeness and comparison purposes. The comparative results showed that the results obtained from the finite element analysis correlate reasonably well, and that these are relatively consistent for the five stub–column specimens evaluated.